Rizal, The Social Portraitist - Emmanuel Jeric A. Albela; Antonio C. Hila (Philippine Social Science Journal, 2020)
This paper attempts to direct on how to understand the two famous novels of Rizal – Noli Me Tangere and El Filibusterismo – within the context of Rizal's intent to expose the social ills of his time. With the use of Charles Derbyshire's translations of The Social Cancer and The Reign of Greed, the researchers explain and show the essential details of the novels and how they reflect historical, social realities as exposed in literary terms – using allegory as synthesis. It includes a re-assessment of the characters in both novels, the key places in the story, conflicts, and how these conflicts are resolved towards the end. The study conveys how Rizal expressed his reflections on and critique of the Philippine society through character and institutional symbolisms. Using historical hermeneutics as a method of the study, the researcher will keep an eye on the available sources and collections of literature, thereby putting the novels in their proper contexts, which properly define Rizal as a novelist and a social critic.